THE INGENIOUS STUDY ON THE FORMULATION OF THERMAL STABILITY BIO-BASED GREASE (Jurnal Teknologi (Sciences & Engineering), 2025)
Concerns about the dwindling supply of mineral oil, which is heavily used in products like grease, have prompted the exploration of Waste Cooking Oil (WCO) as a viable alternative. WCO, derived from improperly disposed vegetable oil, is the focus of this study, which aims to produce grease using Fumed Silica (F.S.) as a thickener. The process involves heating and filtering WCO to reduce moisture content and remove impurities, followed by formulation with additives using a homogenizer at 5000 rpm for three hours, and then cooling for a week. The resulting greases are tested for consistency, oil bleeding, separation, dropping point, and corrosion rate. All lubricants exhibit NLGI values between 00 and 4, oil bleeding from -15% to 15%, oil separation below 4%, a dropping point exceeding 350℃, and a slightly tarnished appearance against copper strips for corrosion classification. An exception is made for F.G94 due to its abnormal grease structure. Despite this anomaly, F.G90 emerges as the top-performing grease, meeting all specifications. This study highlights the effectiveness of WCO as a base oil for grease production.